2016
DOI: 10.22159/ajpcr.2017.v10i1.15073
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of Haematococcus Pluvialis Against Diabetes Induced Oxidative Stress and Inflammation in Rats

Abstract: Objective: The aim of this study is to investigate the impact of Haematococcus pluvialis extract against oxidative stress and inflammatory cytokines induced by hyperglycemia in diabetic rats.Methods: Oxidative stress; lipid peroxide (as presented by Malondialdehyde; MDA) and nitric oxide (NO), beside total antioxidant capacity, enzymatic and non-enzymatic antioxidants including reduced glutathione, glutathione peroxidase, and glutathione reductase were evaluated. The inflammatory cytokines; tumor necrosis fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…These findings are consistent with the results of a previous study, in which 7-week administration of green coffee bean extract could decrease FPG, profile lipid, and blood pressure and improved adiponectin level and HOMA-IR index [26]. In addition, diabetic rats treated with Haematococcus pluvialis extract showed significant improvement in oxidative stress, enhanced antioxidant status, and inflammatory cytokines induced by hyperglycemia in diabetic rats [27]. These results imply that the treatment with puguntano may improve glucose metabolism and ameliorate insulin resistance and inflammation through adiponectin and AdipoR in patients with T2DM.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are consistent with the results of a previous study, in which 7-week administration of green coffee bean extract could decrease FPG, profile lipid, and blood pressure and improved adiponectin level and HOMA-IR index [26]. In addition, diabetic rats treated with Haematococcus pluvialis extract showed significant improvement in oxidative stress, enhanced antioxidant status, and inflammatory cytokines induced by hyperglycemia in diabetic rats [27]. These results imply that the treatment with puguntano may improve glucose metabolism and ameliorate insulin resistance and inflammation through adiponectin and AdipoR in patients with T2DM.…”
Section: Discussionsupporting
confidence: 92%
“…It was indicated that H. pluvialis species is well known for its high content of the strong antioxidant astaxanthin (ATX) that can be protective against several kinds of oxidative damage. 9 , 10 …”
Section: Introductionmentioning
confidence: 99%
“…It is significant that a fructose feed of 10 g/d influenced such chronic changes in serum creatinine and increased urine excretion. Oxidative stress helps to accelerate pathological conditions in diabetes [22][23][24] and promotes the rate of protein glycation [25,26]. So, we attempted to study the effect of probiotics and glycation inhibitor AMG on ROS formation, antioxidant status and tissue fluorescence.…”
Section: Discussionmentioning
confidence: 99%